- #1

- 20

- 0

## Main Question or Discussion Point

This theorem (if it is proven) comes also from a formula of kinetic energy.

Has anyone some suggestions about this one.

Definition of f(n):

[tex]

\ f(n)=(2^{n-1}a)Mod(a+b)

[/tex]

Definition of g(n):

[tex]\

\ g(n)= 4f(n)-2(a+b)+1

[/tex]

Definition of h(n):

[tex]

\ h(n)= Sign(f(n))(Sign(g(n))+1)

[/tex]

Theorem:

[tex]

\lim_{n\rightarrow\infty}\sum_{k=1}^{n}{h(k)\left(\frac{1}{2}\right)^{k+1}} = \frac{a}{(a+b)}

[/tex]

Thank you for trying.

Has anyone some suggestions about this one.

Definition of f(n):

[tex]

\ f(n)=(2^{n-1}a)Mod(a+b)

[/tex]

Definition of g(n):

[tex]\

\ g(n)= 4f(n)-2(a+b)+1

[/tex]

Definition of h(n):

[tex]

\ h(n)= Sign(f(n))(Sign(g(n))+1)

[/tex]

Theorem:

[tex]

\lim_{n\rightarrow\infty}\sum_{k=1}^{n}{h(k)\left(\frac{1}{2}\right)^{k+1}} = \frac{a}{(a+b)}

[/tex]

Thank you for trying.